2015
DOI: 10.1186/s40479-014-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal course of non-suicidal self-injury and deliberate self-harm: a systematic review of the literature

Abstract: Non-suicidal self-injury (NSSI) has been proposed as diagnostic entity and was added to the section 3 of the DSM 5. Nevertheless, little is known about the long-term course of this disorder and many studies have pointed to the fact that NSSI seems to be volatile over time. We aimed to assemble studies providing longitudinal data about NSSI and furthermore included studies using the definition of deliberate self-harm (DSH) to broaden the epidemiological picture. Using a systematic search strategy, we were able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
366
6
32

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(440 citation statements)
references
References 46 publications
36
366
6
32
Order By: Relevance
“…NSSI typically emerges between the age of 12-15 years, and recent reviews suggest that as many as 18% of adolescent community-based samples engage in NSSI (Muehlenkamp et al, 2012;Plener et al, 2015;Swannell et al, 2014) and as many as 37% of clinical samples meet the DSM-5 criteria for NSSI-disorder In-Albon et al, 2013). Although exposure to direct forms of childhood maltreatment (i.e., physical abuse, sexual abuse) is among the most widely studied risk factors for NSSI, research on NSSI has largely overlooked the role of exposure to indirect forms of child maltreatment.…”
mentioning
confidence: 94%
“…NSSI typically emerges between the age of 12-15 years, and recent reviews suggest that as many as 18% of adolescent community-based samples engage in NSSI (Muehlenkamp et al, 2012;Plener et al, 2015;Swannell et al, 2014) and as many as 37% of clinical samples meet the DSM-5 criteria for NSSI-disorder In-Albon et al, 2013). Although exposure to direct forms of childhood maltreatment (i.e., physical abuse, sexual abuse) is among the most widely studied risk factors for NSSI, research on NSSI has largely overlooked the role of exposure to indirect forms of child maltreatment.…”
mentioning
confidence: 94%
“…Another longitudinal study by Marshall et al (2013) found that depressive symptoms at Time 1 significantly predicted NSSI at Times 2 and 3. For a detailed review of the literature on the association between depressive symptoms and NSSI among adolescents, we refer the reader to Plener et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime prevalence of suicide attempts among adults and adolescents is approximately 1.9 to 8.7% and 3.1 to 8.8% respectively (Nock et al, 2008). Both NSSI and suicide attempts are associated with numerous negative life outcomes and have significant economic and social consequences (Goldman-Mellor et al, 2014; Plener, Schumacher, Munz, & Groschwitz, 2015; Shepard, Gurewich, Lwin, Reed, & Silverman, 2016). …”
Section: Introductionmentioning
confidence: 99%